THE IDENTIFICATION OF WOOD CRITERIA USED IN MAKING REPLICA OF ISTANO BASA PAGARUYUNG BASED ON PUBLIC PERCEPTION OF BATUSANGKAR CITY - Esa Ervina; Yossi Oktorini; Rudianda Sulaeman (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2017)
The Replica of Istano Basa Pagaruyung is Minangkabau traditional house building in the form of a rumah gadang which is made with the guiding of the palace that ever existed before. Istano Basa Pagaruyung has been destroyed three times in the year 1837 due to the war, in 1996 and in 2007 due to burning. The existence and preservation of this traditional house must be maintained because it is a cultural symbol of Minangkabau society. This study aims to determine the type and criteria of wood used in making replica Istano Basa Pagaruyung based on public perception. This study uses snowball sampling method that has been implemented in October 2016 in Replica Istano Basa Pagaruyung. Criteria of wood used as raw material for reproduction of Istano Pagaruyung based on community perception that is hardwood, straight and have dark color. Under construction, the wood used should not be wet. Wood cutting system that is wood can not be felled in a flowering state, because at the time the wood has a delicious smell so favored by insects. Types of wood used are Toona sureni, Shorea leprosula Miq., Anisoptera costata Korth and Ptetospermum spp.